SINKRONISASI FORMAT FLIGHT STRIP CONTENT ASRT PADA CLIENT BRIEFING OFFICE ATC SYSTEM - Okta , I Made Okta Dwipayana; Wildan, Muh (Jurnal Penelitian, 2024)
This research was conducted qualitatively with descriptive data analysis techniques and data collection using interviews and participant observation. The purpose of this study is to analyze the causes of ASRT features that do not appear on the FDD stack stack stack electronic table in AMC ATC System after installation and restart-ing at Perum LPPNPI (Airnav Indonesia) Denpasar Branch. I Gusti Ngurah Rai Airport. The method of data collection through direct damage observation and company data source is the ATC System Equipment Manual Book. The ASRT (Actual Start-Up Request Time) feature is a feature used by ATC (Air Traffic Controller) for time recording if between the time of the aircraft start request and the implementation of its realization there is a delay or time difference when taking off / landing. Through this research, it was found that the flight strip configuration for the client Briefing Office at AMC has its own security and configuration files so that the flight strip in the BO (Briefing Office) cannot change according to file changes that cause the ASRT feature not to appear. To overcome this, the author and data source synchronize the ATC workstation system and make improvements to the config file of the new ASRT feature. Until the final result is obtained, the ASRT feature appears and can be used properly.